345 Analysis of Antioxidative Status of Human Milk and its Variations at Day and Night Time. (October 2012) - Bagci, S; Pauli, L; Reinsberg, J; Zur, B; Bartmann, P; Mueller, A
Abstract : Introduction: Human milk (HM) contains antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase. Melatonin (MT) shows antioxidative properties both directly by stimulating the activities of antioxidant enzymes and indirectly by scavenging free radicals. The aim of this study was to evaluate the effect of MT status on the level of SOD, GSH-Px 3 and the total antioxidant capacity (TAC) of HM. Material and Methods: 114 samples of HM were collected from 22 healthy women during daytime (DT; 10a.m.-9.59p.m.) and nighttime (NT; 10p.m.-9.59a.m.). MT, SOD, GSH-Px3 levels and TAC were assayed and compared between DT-HM and NT-HM. Moreover, the Pearson's correlation coefficient was calculated between MT and SOD, GSH-Px3 and TAC. Results: MT showed a circadian rhythm with high levels at NT and low levels at DT (mean± SEM; 9.2±1.2 vs. 2.0±0.3 pg/ml, respectively, p<0.0001), while SOD, GSH-Px3 and TAC had no circadian changes in HM (p>0.05). There was no correlation between MT levels and SOD, GSH-Px3 levels and TAC. Conclusion: The MT status influence neither SOD and GSH-Px3 levels nor TAC of HM. It should be pointed that our results represent only the effect of MT on the extracellular component of the antioxidant system and it does not exclude the possibility that high MT concentrations in HM may induce the intracellular and mitochondrial antioxidant enzyme system in the gastrointestinal tract.